1977
DOI: 10.1007/bf02012778
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of matrix vesicles in epiphyseal cartilage

Abstract: The in vivo metabolism of 32P orthophosphate into phospholipids of chondroxyte, matrix vesicle, and membrane fractions of chicken epiphyseal cartilage has been studied. Incorporation of radioactive phosphate into the total phospholipid fraction of matrix vesicles was rapid, the labeling of phosphatidylcholine and lysophosphatidylserine being even more rapid in matrix vesicles than in chondrocytes. These findings indicate that matrix vesicles are formed by a rapid, metabolically active process, and are not remn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…They transverse the PG envelope and terminate in the territorial matrix. They may play a role in the release of collagen precursors and other matrix components and in the segregation of matrix vesicles (Wuthier et al, 1977;Schenk et al, 1982). The ITM is thought to facilitate diffusion in the longitudinal direction, especially from the nutritive vessels along its epiphyseal surface toward the metaphysis.…”
Section: Discussionmentioning
confidence: 99%
“…They transverse the PG envelope and terminate in the territorial matrix. They may play a role in the release of collagen precursors and other matrix components and in the segregation of matrix vesicles (Wuthier et al, 1977;Schenk et al, 1982). The ITM is thought to facilitate diffusion in the longitudinal direction, especially from the nutritive vessels along its epiphyseal surface toward the metaphysis.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies on the incorporation of 32 Pi into phospholipids of chondrocytes and MV have revealed that MV formation is a dynamic process in which labeling of MV PC and PE -which tend to be depleted -was nearly as rapid as that of the cellular lipids. In contrast, labeling of PS and SM -which are enriched in MV -was significantly slower (398). This paradox suggests that MV formation involves processes in which the plasma membrane becomes modified by action of phospholipases that selectively degrade PC and PE, while retaining PS and SM.…”
Section: Phospholipid Metabolic Studiesmentioning
confidence: 94%
“…Membranous vesicles also occur in fibrocartilage, but these are linked with cell disintegration (Ghadially et al, 1978b) rather than the metabolically active process postulated for epiphyseal cartilage (Wuthier et al, 1977). We do not think they have been isolated from elastic and fibrocartilage or examined in association with the chondrocytes by SEM.…”
Section: E Matrix Vesiclesmentioning
confidence: 95%